A Facile Carbon Coating on Mg‐Embedded SiOx Alloy for Fabrication of High‐Energy Lithium‐Ion Batteries. Issue 30 (9th September 2022) - Mukhan, Orynbassar; Umirov, Nurzhan; Lee, Byoung‐Min; Yun, Ji‐Su; Choi, Jae‐Hak; Kim, Sung‐Soo
Abstract: The use of SiO x ‐containing anode materials to increase the energy density limited by the utilization of low gravimetric specific capacity commercial graphite has recently received great interest. However, a low initial Coulombic efficiency and other inherent disadvantages of SiO x such as huge volume changes and poor electron transportation result in complicating its widespread use. To overcome these issues herein, a simple, cost‐effective, and mass‐producible phenolic resin‐coated Mg‐SiO x anode composite for high‐performance lithium‐ion batteries compared to the carbon film produced by the chemical vapor deposition method is designed. Carbon‐coated Mg‐SiO x based on the phenolic resin is found to act as a direct contact protection electrolyte–electrode interface and boosts kinetics of Li + transport among the electrodes, ensuring the formation of stable solid electrolyte interphase upon cycling. As a result, the phenolic resin‐coated Mg‐SiO x alloy electrode delivers a stable specific capacity up to ≈1700 mAh g ‐1 after 100 cycles. Testing with an industrial protocol, a full cell pairing of the Mg‐SiO x @C/graphite blended anode and commercial LiNi0.8 Mn0.1 Co0.1 O2 cathode achieves a gravimetric and volumetric energy density of 467 Wh Kg ‐1 and 953 Wh L ‐1, respectively, which is higher than that of the cell based on the conventional graphite. Abstract : This research is empirically examined and shows outstanding performance as negative electrode for lithium‐ion battery. A simple approach to uniformly coating nano‐Si embedded in Mg‐doped SiO x matrix with carbon. Synthesize process, physical, and electrochemical properties' analysis prove the practical significance of the current approach for further commercialization of high‐performance SiO x alloys.